Efek Hepatoprotektor Ekstrak Daun Dandang Gendis (Clinacanthus nutans) terhadap Kadar SGPT Tikus Putih (Rattus novergicus) yang Diinduksi Parasetamol - Sasongko, Devi Purnamasari; Subandono, Jarot; ., Martini (Nexus Kedokteran Translasional, 2012)
Background: Paracetamol was a safe drug, but would cause oxidative stress ifÂ  taken too much.. Dandang gendis leaves contained a flavonoid antioxidant. This research intended to prove the antioxidant effect of dandang gendis leaves that could prevent liver cell damage of white rat induced by paracetamol. Methods: This research was an experimental laboratoric with post test only control group design. This research had taken place at Parasitology and Micology Faculty of Medicine Sebelas Maret University Surakarta. The sample was 32Â  Wistar white rats. The dependent variable was the SGPT level of white rats and the independent variable was the dandang gendis leaves extract. The white rats were divided into 4 groups: negative control group (KK0), positive control group (KK1), first threated group (KP1), and second threated group (KP2). KP1 had been given 30 mg/200 gr BB dose and KP2 had been given 60 mg/200 gr BB dose for 14 days. At 11th âÂ  13th days, the white rats from KK1, KP1, and KP2 had been given 291.6 mg/200 gr BB dose of paracetamol. At 14th day, ratâs blood had been taken from orbitalis sinus. The damage of the liver cell had been measured with SGPT laboratory test. The data had been analyzed with one way ANOVA test then with post hoc test (Î± = 0.05). Results: The highest rate of SGPT levels was KK1, following KP1, KP2, and the lowest was KK0. Oneway ANOVA test resuls showed a significant difference among the four groups with p = 0.000. Post hoc test results showed a significant difference between KK0 â KK1 (p = 0.003) and KK0 â KP2 (p = 0.019) whereas between KK0 â KP1 (p = 0.204), KK1 â KP1 (p = 0.885), KK1 â KP2 (p = 0.077), and KP1 â KP2 (p = 0.932) had no significant difference. Conclusion: Giving dandang gendis leaves extract was notÂ  significant to raise the SGPT level of white rat induced by paracetamol. Raising dandang gendis leaves extract doses was not significant to raise its hepatoprotector effect. Keywords: dandang gendis leaf, SGPT, white rat, hepatoprotector, paracetamol